2022
DOI: 10.1021/acsomega.2c03062
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation and Comparison of Machine Learning Methods in QSAR Modeling of Antioxidant Tripeptides

Abstract: Due to their multiple beneficial effects, antioxidant peptides have attracted increasing interest. Currently, the screening and identification of bioactive peptides, including antioxidative peptides based on wet-chemistry methods are time-consuming and highly rely on many advanced instruments and trained personnel. Quantitative structure–activity relationship (QSAR) analysis as an in silico method can be more efficient and cost-effective. However, model performance of QSAR studies on ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Feature importance of these variables in ABTS radical scavenging capacity model development and ORAC model development showed that N-terminus residues played a more important role in antioxidant activity. In the study of Chen et al, the variable importance in projection (VIP) values revealed that the C-terminus had greater contribution to the ABTS radical scavenging capacity of tripeptides, and such an observation was also confirmed in the study of Du et al It is interesting that antioxidant dipeptides showed a different pattern where the importance of the N-terminus was greater than that of the C-terminus. This is consistent with the VIP values from the partial least-squares regression (PLSR) models in Zheng et al, although they instead further emphasized the importance of tyrosine and tryptophan at the N-terminus .…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…Feature importance of these variables in ABTS radical scavenging capacity model development and ORAC model development showed that N-terminus residues played a more important role in antioxidant activity. In the study of Chen et al, the variable importance in projection (VIP) values revealed that the C-terminus had greater contribution to the ABTS radical scavenging capacity of tripeptides, and such an observation was also confirmed in the study of Du et al It is interesting that antioxidant dipeptides showed a different pattern where the importance of the N-terminus was greater than that of the C-terminus. This is consistent with the VIP values from the partial least-squares regression (PLSR) models in Zheng et al, although they instead further emphasized the importance of tyrosine and tryptophan at the N-terminus .…”
Section: Resultsmentioning
confidence: 79%
“…Technically, R 2 CV could not describe the model’s performance in an unknown data set because the data used to obtain R 2 CV were used in model building . In this study, a much larger data set was collected from the latest publications, and feature selection with nonlinear regression modeling approaches was employed to link the data set and antioxidant activity, which all contributed to the better performance in test data sets. ,,,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction of the structural activity relationship (SAR) [ 1 , 2 ] information from chemical datasets relies on the pairwise structural comparison of all toxicophore features and small molecules, which highlights the degree of the structural relationship between the compounds [ 3 , 4 , 5 , 6 ]. The Quantitative Structure–Activity Relationship (QSAR) can correlate the compound’s chemical and structural features with its physicochemical or biological properties.…”
Section: Introductionmentioning
confidence: 99%